Doped graphene for metal-free catalysis - Kong, Xiang-Kai; Chen, Chang-Le; Chen, Qian-Wang (Chemical Society reviews, 2014)
Graphene has attracted increasing attention in different scientific fields including catalysis. Via modification with foreign metal-free elements such as nitrogen, its unique electronic and spin structure can be changed and these doped graphene sheets have been successfully employed in some catalytic reactions recently, showing them to be promising catalysts for a wide range of reactions. In this review, we summarize the recent advancements of these new and interesting catalysts, with an emphasis on the universal origin of their catalytic mechanisms. We are full of hope for future developments, such as more precisely controlled doping methods, atom-scale surface characterization technology, generating more active catalysts via doping, and finding wide applications in many different fields. This review covers the latest advances in doped graphene for metal-free catalysis.